2004
DOI: 10.1080/14015430410033218
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of alaryngeal voice and speech

Abstract: The aim of the research was to compare voice and speech in three groups of alaryngeal speakers: 1) patients using esophageal speech, 2) patients with electro-acoustical speech aids and 3) patients with voice prostheses. Acoustic analysis and pronunciation tests were used for the analysis. Acoustic analysis included fundamental frequency, maximum phonation time, jitter, shimmer and intensity. Pronunciation parameters were: phonetic block duration, number of syllables in a phonetic block, rate of speech, maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 17 publications
2
21
0
5
Order By: Relevance
“…Using several parameters, studies have found esophageal voice to have characteristics indicative of significantly poorer quality than alternative forms of alaryngeal speech and normal speech. [2][3]5 However, studies using perturbation measures for analysis of extremely aperiodic voices such as esophageal voice seldom quantify the reliability of results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using several parameters, studies have found esophageal voice to have characteristics indicative of significantly poorer quality than alternative forms of alaryngeal speech and normal speech. [2][3]5 However, studies using perturbation measures for analysis of extremely aperiodic voices such as esophageal voice seldom quantify the reliability of results.…”
Section: Discussionmentioning
confidence: 99%
“…Signalto-noise ratio, fundamental frequency, and intensity values were found to be lower and jitter and shimmer values were found to be higher in esophageal speech than in laryngeal speech. [2][3]5 However, recent research suggests that the validity of perturbation analysis is highly questionable when these measures are applied to aperiodic signals. [6][7] In contrast, nonlinear dynamic methods of acoustic analysis have shown potential to reliably quantify both periodic and aperiodic signals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lung air is directed toward the esophagus, through the vocal prosthesis, and the sound source vibrates, which is labeled as pharyngoesophageal segment (PES). Because this makes it possible to use the flow of the lung air, the TE voice approximates the speech fluency and speed of the laryngeal voice (6,7) . In the meantime, the irregular vibration of the PES, which is evident, generates a voice quality quite rough, with low pitch (8,9) and which is different, when compared with the laryngeal voice (10,11) .…”
Section: Introductionmentioning
confidence: 99%